1965
DOI: 10.2466/pms.1965.20.2.549
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time as a Function of Onset and Offset Stimulation of the Fovea and Periphery

Abstract: Reaction times were obtained for the onset and offset of luminous stimuli of 31,400 mL., 314 mL., 3.14 mL., and 1.98 mL., presented in the fovea and periphery. It was found that in the periphery offset RTs are longer than onset RTs. The opposite is true for the fovea. In both the fovea and periphery the differences between the onset and offset RTs decrease as the luminance increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1970
1970
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Bartlett, Stieht, and Pease (1968) and Pease and Sticht (1965) found the same result with small foveal stimuli lasting for between 2 and 4 sec. However, persistences of up to about 80 msec are found with the onset RT/offset RT method if either: (a) the stimuli are peripheral (Bartlett, Sticht, & Pease, 1968;Pease & Stieht, 1965), even with long-duration stimuli; or (b) the stimuli are brief (Briggs & Kinsbourne, 1972), even with foveal stimuli.…”
Section: The Onset/offset Reaction Time Techniquesupporting
confidence: 63%
See 2 more Smart Citations
“…Bartlett, Stieht, and Pease (1968) and Pease and Sticht (1965) found the same result with small foveal stimuli lasting for between 2 and 4 sec. However, persistences of up to about 80 msec are found with the onset RT/offset RT method if either: (a) the stimuli are peripheral (Bartlett, Sticht, & Pease, 1968;Pease & Stieht, 1965), even with long-duration stimuli; or (b) the stimuli are brief (Briggs & Kinsbourne, 1972), even with foveal stimuli.…”
Section: The Onset/offset Reaction Time Techniquesupporting
confidence: 63%
“…If the pupil is not fully dilated, higher luminances would be required to reach this level of retinal illumination. Referring back to the various studies of visible persistence described earlier, and taking into account the use of artificial pupils in several of them and of light-adapted subjects in others, these calculations indicate that a retinal illuminance of 3 log Td was not approached in any of these studies except in some of the conditions of two of the studies using the reaction time technique (Pease & Sticht, 1965;Rains, 1961).…”
Section: Stimulus Luminance Retinal Illumination and Rod Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pease and Sticht (1965) have reported that reaction time to the onset and to the offset of a visual stimulus is influenced by the location, fovea or periphery, of the signal. Also, Grondin and Rousseau (1991) have reported that having the second marker of an A-V sequence delivered at the periphery rather than at fovea greatly reduces the perceived duration of such a sequence; along the same line, they also have reported that, in a V-A sequence, the perceived duration is much shorter when the first marker is delivered from the periphery rather than from fovea.…”
Section: Resultsmentioning
confidence: 99%
“…However, he suggested that differences may appear when a small, dim peripheral flash is employed. Pursuing this suggestion, Pease and Sticht (1965) investigated RT as a function of onset, offset, location and luminance of visual stimuli presented either foveally or peripherally. When stimuli were presented to the periphery, R T was significantly longer for the offset of the scimulus than for the onset.…”
mentioning
confidence: 98%